Method for preparing microcrystalline glass, microcrystalline glass and application of microcrystalline glass

By combining heavy alcohol incineration ash with gasification furnace slag, along with flux and nucleating agent, the melting and sintering temperatures of glass-ceramics were reduced, solving the problem of high production costs and achieving effective resource utilization and improved product performance.

CN119263641AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310820052.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

The high melting temperature and high production cost of existing microcrystalline glass preparation methods have limited their development.

Method used

The method utilizes a combination of high-sodium, low-silicon heavy alcohol incineration ash and high-silicon, low-calcium gasification slag, along with flux and nucleating agents. By reducing the melting and sintering temperatures through the melting and roasting processes, the amount of imported or chemical raw materials can be reduced.

Benefits of technology

It effectively reduces the production cost of microcrystalline glass, while realizing the harmless, reduced-volume, and resource-based disposal of re-incineration ash and gasification slag, and improving the density, hardness, and compressive strength of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263641A_ABST
    Figure CN119263641A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a method for preparing microcrystalline glass, the microcrystalline glass and application of the microcrystalline glass. The method comprises the following steps: (1) mixing the heavy alcohol incineration ash, waste glass, gasification furnace slag, a fluxing agent and a nucleating agent, melting and cooling to obtain glass slag, with the melting temperature being 1100-1400 DEG C; and (2) the glass slag and the heavy alcohol incineration ash are mixed, roasted and cooled, the microcrystalline glass is obtained, and the roasting temperature ranges from 800 DEG C to 1000 DEG C. According to the invention, the high-sodium low-silicon heavy alcohol incineration ash and the high-silicon low-calcium gasification slag are subjected to advantage compatibility, so that the melting temperature can be reduced, formation of Na-Al-Si series glass ceramics is facilitated, and the addition amount of foreign ores or chemical raw materials can be reduced; in the sintering process, the heavy alcohol incineration ash is added for the second time, the sintering temperature can be reduced, and the energy consumption in the glass ceramic preparation process can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a method for preparing microcrystalline glass, microcrystalline glass and applications thereof. Background Art

[0002] Glass-ceramics, also known as glass ceramics or microcrystalline ceramics, is a polycrystalline composite material with uniform distribution of glass phase and microcrystalline phase, which is obtained by controlling crystallization of basic glass with specific composition during heat treatment. Compared with traditional glass, it has high softening temperature, excellent thermal stability and chemical stability, high mechanical strength and hardness. Compared with ceramics, the grains and microstructure of glass-ceramics are more uniform and dense, with almost no pores, and the product surface is smooth. Therefore, glass-ceramics has both the basic properties of glass and the polycrystalline characteristics of ceramics, and concentrates the advantages of both glass and ceramics. It is a new type of inorganic polycrystalline solid material with excellent performance and controllable structural composition.

[0003] The raw materials of microcrystalline glass can be general glass raw materials, or they can be various bulk industrial solid wastes such as slag, tailings, ash, fly ash, etc. These solid wastes contain silicon, aluminum, calcium, magnesium, iron, etc. for the preparation of microcrystalline glass. Using these wastes as raw materials to prepare microcrystalline glass can not only reduce pollution to the environment, but also generate certain economic value. Ash and gasification slag after hazardous waste incineration are common hazardous wastes and solid wastes in the petrochemical industry, and their proper disposal has received increasing attention. Among them, the ash from the incineration of petrochemical hazardous waste contains a large amount of sodium, and the gasification slag contains silicon, calcium, aluminum, iron and other elements. By combining the two to advantage, a ash with a chemical composition that meets the requirements for the preparation of Na-Ca-Al-Si series microcrystalline glass can be obtained.

[0004] At present, the common methods for preparing microcrystalline glass mainly include melting method, sintering method and sol-gel method. The melting method is the earliest method used to prepare microcrystalline glass and is also the most mature method at present. Its characteristics are simple process, continuous production, high mechanical properties of products, and its disadvantages are high energy consumption, difficult to control the crystallization process, and easy explosion of products. The sintering method is to grind the base glass into particles, and then sinter and sublimate the crystal form under an appropriate heat treatment system to obtain microcrystalline glass. The sintering method has a low treatment temperature and low energy consumption, but the product has more pores inside and poor density. The sol-gel method is a new preparation method, which is to add certain metal compounds, hydrolyze at a lower temperature to generate gel powder, and then turn the gel powder into microcrystalline glass through a certain heat treatment system. The crystals of microcrystalline glass prepared by the sol-gel method can reach the nanometer level. The disadvantage is that the preparation cost is too high, and shrinkage will occur during the sintering process, causing the microcrystalline glass to deform.

[0005] Chinese patent application CN104496186 A discloses a cordierite-based nano-ceramic glass and its preparation method, including a main component, a crystal nucleating agent, a regulator and a flux, wherein the main component includes SiO2, MgO and Al2O3; the crystal nucleating agent includes one or more of TiO2, ZrO2 and P2O5, and is prepared by a melting method, with a nucleation temperature of 500°C to 700°C, and a crystallization temperature of 1050 to 1200°C. Chinese patent application CN102838283 A discloses a method and product for producing foamed microcrystalline glass using composite industrial waste residues, characterized in that different industrial waste residues are crushed, mixed and ground into raw material powder in proportion, the raw material powder is heated to melt, quenched, dried and then ground into mature material, and then a crystal nucleating agent, a foaming agent, a foam stabilizer, a flux and a reinforcing agent are added to form a foamed microcrystalline glass batch, and the batch is pressed and formed, and then preheated, foamed, foam stabilized and annealed to obtain a foamed microcrystalline glass after firing.

[0006] At present, whether pure substances or industrial waste residues are used to prepare microcrystalline glass, there are problems of high melting temperature and high production cost, which limits the development of microcrystalline glass. Therefore, how to reduce the production cost of microcrystalline glass is an important issue that the microcrystalline glass industry needs to solve urgently. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of high melting temperature and high production cost in the existing methods for preparing microcrystalline glass, and to provide a method for preparing microcrystalline glass, microcrystalline glass and its application. The method advantageously combines high-sodium and low-silicon heavy alcohol incineration ash with high-silicon and low-calcium gasification furnace slag to reduce the melting temperature. At the same time, adding heavy alcohol incineration ash during the sintering process can reduce the sintering temperature, thereby reducing the production cost.

[0008] In order to achieve the above object, the present invention provides a method for preparing glass-ceramics, which comprises the following steps:

[0009] (1) mixing, melting and cooling heavy alcohol incineration ash, waste glass, gasification furnace slag, flux and crystal nucleating agent to obtain glass molten slag, wherein the melting temperature is 1100-1400° C.;

[0010] (2) mixing the glass slag and heavy alcohol incineration ash, roasting and cooling to obtain glass-ceramics, wherein the roasting temperature is 800 to 1000° C.;

[0011] Wherein, the heavy alcohol incineration ash contains 50-85 weight % of Na2CO3 and 5-20 weight % of SiO2;

[0012] The gasification slag contains 20 to 45 wt % of SiO2, 10 to 25 wt % of CaO and 8 to 15 wt % of Al2O3.

[0013] Preferably, the heavy alcohol incineration ash contains 50-85 weight % of Na2CO3, 5-20 weight % of SiO2, 5-10 weight % of NaCl and 2-10 weight % of Fe2O3.

[0014] Preferably, the gasification slag contains 20-45 wt% SiO2, 10-25 wt% CaO, 8-15 wt% Al2O3, 5-15 wt% Fe2O3 and 3-37 wt% residual carbon.

[0015] Preferably, in step (1), based on the total weight of heavy alcohol incineration ash, waste glass, gasification slag, flux and crystal nucleating agent, the content of the heavy alcohol incineration ash is 20-40% by weight, the content of the waste glass is 25-30% by weight, the content of the gasification slag is 25-30% by weight, the content of the flux is 5-10% by weight, and the content of the crystal nucleating agent is 5-10% by weight.

[0016] Preferably, in step (1), the flux is selected from one or more of B2O3, Na2O, K2O, CaO and BaO.

[0017] Preferably, in step (1), the nucleating agent is selected from one or more of Fe2O3, ZrO2, NaF, Cr2O3 and TiO2.

[0018] Preferably, in step (1), the melting conditions include: melting temperature of 1200-1300°C; melting time of 30-150 min, preferably 60-120 min; heating rate of 5-20°C / min, preferably 10-15°C / min.

[0019] Preferably, step (1) comprises: mixing and grinding heavy alcohol incineration ash, waste glass, gasification furnace slag, flux and crystal nucleating agent, and then melting, cooling and drying the obtained raw powder to obtain glass slag.

[0020] Preferably, the particle size of the raw powder obtained by grinding is 25 to 106 μm, preferably 45 to 75 μm.

[0021] Preferably, the cooling method is water quenching or natural cooling.

[0022] Preferably, the drying temperature is 90-120°C.

[0023] Preferably, in step (2), based on the total weight of the glass slag and the heavy alcohol incineration ash, the content of the glass slag is 65-95% by weight, and the content of the heavy alcohol incineration ash is 5-35% by weight.

[0024] Preferably, the calcination conditions include: calcination temperature of 850-950° C.; calcination time of 60-150 min, preferably 90-120 min; heating rate of 5-15° C. / min, preferably 8-10° C. / min.

[0025] Preferably, step (2) comprises: mixing the glass slag and heavy alcohol incineration ash and grinding them, and then roasting and cooling the obtained glass composite ash to obtain microcrystalline glass.

[0026] Preferably, the particle size of the glass composite ash obtained by grinding is 25 to 106 μm, preferably 45 to 75 μm.

[0027] The second aspect of the present invention provides a glass-ceramic prepared by the method described in the first aspect.

[0028] Preferably, the density of the microcrystalline glass is 2.08-2.43 g / cm 3 , Vickers hardness is 4.01~4.43GPa, and compressive strength is 223~261Mpa.

[0029] The third aspect of the present invention provides a use of the microcrystalline glass described in the second aspect as a building decoration material.

[0030] The present invention advantageously combines high-sodium and low-silicon heavy alcohol incineration ash with high-silicon and low-calcium gasification slag to prepare basic glass, which can reduce the melting temperature, is more conducive to the formation of Na-Al-Si series microcrystalline glass, and can reduce the amount of foreign ore or chemical raw materials added; under preferred conditions, B2O3 is added as a flux and TiO2 is added as a crystal nucleating agent in the process of preparing basic glass, which can further reduce the melting temperature. At the same time, adding heavy alcohol incineration ash twice during the sintering process can reduce the sintering temperature, which is conducive to reducing the energy consumption of the microcrystalline glass preparation process.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1. Use heavy alcohol incineration ash and gasification slag as raw materials for the production of microcrystalline glass to achieve harmless, reduced and resourceful disposal of heavy alcohol incineration ash and gasification slag;

[0033] 2. The combination of high-sodium and low-silicon heavy alcohol incineration ash and high-silicon and low-calcium gasification slag is more conducive to the formation of Na-Al-Si series microcrystalline glass, which can reduce the addition of foreign ores or chemical raw materials;

[0034] 3. Adding high-sodium heavy alcohol incineration ash during the sintering process is beneficial to reducing the energy consumption of the microcrystalline glass preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a flow chart of preparing microcrystalline glass according to the present invention. DETAILED DESCRIPTION

[0036] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0037] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0038] A first aspect of the present invention provides a method for preparing glass-ceramics, the method comprising the following steps:

[0039] (1) mixing, melting and cooling heavy alcohol incineration ash, waste glass, gasification furnace slag, flux and crystal nucleating agent to obtain glass molten slag, wherein the melting temperature is 1100-1400° C.;

[0040] (2) The glass slag and heavy alcohol incineration ash are mixed, roasted, and cooled to obtain microcrystalline glass, wherein the roasting temperature is 800-1000°C.

[0041] In the method of the present invention, heavy alcohol incineration ash containing specific components and gasification furnace slag containing specific components are synergistically mixed with waste glass, flux, and crystal nucleating agent to prepare glass slag (basic glass), which can reduce the melting temperature and reduce the cost. At the same time, when the glass slag is further roasted to prepare microcrystalline glass, adding heavy alcohol incineration ash again can reduce the roasting temperature.

[0042] According to the present invention, specifically, the heavy alcohol incineration ash contains 50-85 weight % of Na2CO3 and 5-20 weight % of SiO2; the gasification slag contains 20-45 weight % of SiO2, 10-25 weight % of CaO and 8-15 weight % of Al2O3.

[0043] More specifically, the heavy alcohol incineration ash mainly contains 50-85 wt% of Na2CO3, 5-20 wt% of SiO2, 5-10 wt% of NaCl and 2-10 wt% of Fe2O3. In addition, the heavy alcohol incineration ash also contains a small amount of other components, such as K2O, Al2O3 and MgO.

[0044] More specifically, the gasification slag mainly contains 20-45 wt % of SiO2, 10-25 wt % of CaO, 8-15 wt % of Al2O3, 5-15 wt % of Fe2O3 and 3-37 wt % of residual carbon.

[0045] In the method of the present invention, the waste glass is common waste glass in the art, and its source is not limited. Specifically, the waste glass contains SiO2, CaO, Na2O, Al2O3 and MgO.

[0046] In the method described in the present invention, in order to obtain microcrystalline glass with density, hardness and strength that meet the standards, it is necessary to limit the amount of heavy alcohol incineration ash, waste glass, gasification furnace slag, flux and nucleating agent to an appropriate range.

[0047] In some preferred embodiments, in step (1), based on the total weight of heavy alcohol incineration ash, waste glass, gasification slag, flux and crystal nucleating agent, the content of the heavy alcohol incineration ash is 20-40% by weight, the content of the waste glass is 25-30% by weight, the content of the gasification slag is 25-30% by weight, the content of the flux is 5-10% by weight, and the content of the crystal nucleating agent is 5-10% by weight.

[0048] According to the present invention, the fluxing agent may be selected from conventional ones in the art, as long as it can play a fluxing effect.

[0049] In a specific embodiment, in step (1), the flux is selected from one or more of B2O3, Na2O, K2O, CaO and BaO. In order to further reduce the melting temperature, in a preferred embodiment, the flux is B2O3.

[0050] In the present invention, in a specific embodiment, in step (1), the crystal nucleating agent is selected from one or more of Fe2O3, ZrO2, NaF, Cr2O3 and TiO2. In a preferred embodiment, in step (1), the crystal nucleating agent is Fe2O3 or TiO2.

[0051] In the present invention, since the heavy alcohol incineration ash with high sodium and low silicon and the gasification furnace slag with high silicon and low calcium are advantageously matched, it is more conducive to the formation of Na-Al-Si series microcrystalline glass and the melting temperature is reduced.

[0052] In a specific embodiment, in step (1), the melting temperature may be 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C or 1400°C; preferably, the melting temperature is 1200-1300°C.

[0053] According to the present invention, in step (1), the melting time can be selected conventionally in the art. In a preferred embodiment, the melting time is 30 to 150 min, preferably 60 to 120 min, specifically, for example, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.

[0054] In the present invention, the melting process may include: heating to a melting temperature at a certain heating rate, and then maintaining the melting time at the melting temperature. Specifically, the heating rate may be 5 to 20°C / min, preferably 10 to 15°C / min, such as 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min or 15°C / min.

[0055] In a preferred embodiment, step (1) specifically comprises: mixing and grinding heavy alcohol incineration ash, waste glass, gasification furnace slag, flux and crystal nucleating agent, and then melting, cooling and drying the obtained raw powder to obtain glass slag.

[0056] According to the present invention, specifically, the grinding process is carried out in a planetary ball mill. In a specific embodiment, the particle size of the raw powder obtained by grinding is 25 to 106 μm, preferably 45 to 75 μm.

[0057] According to the present invention, the cooling method can be various cooling methods well known in the art. Specifically, the cooling method can be water quenching or natural cooling. In a preferred embodiment, in order to improve the rigidity and compressive strength of the prepared microcrystalline glass, the cooling method is water quenching.

[0058] In the present invention, the drying method can be a conventional operation in the art, such as drying in a blast drying oven to constant weight. In the present invention, the drying temperature can be a conventional choice in the art, specifically, the drying temperature can be 90 to 120°C, such as 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.

[0059] In the method of the present invention, in order to reduce the roasting temperature without affecting the density, compressive strength and hardness of the microcrystalline glass, in a preferred embodiment, in step (2), based on the total weight of the glass slag and the heavy alcohol incineration ash, the content of the glass slag is 65 to 95% by weight, and the content of the heavy alcohol incineration ash is 5 to 35% by weight.

[0060] According to the present invention, the roasting temperature can be reduced due to the addition of high sodium heavy alcohol incineration ash. In a specific embodiment, in step (2), the roasting temperature can be 800-1000°C; preferably, the roasting temperature is 850-950°C, for example, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C or 950°C.

[0061] In a specific embodiment, in step (2), the calcination time can be 60 to 150 min, preferably 90 to 120 min, for example 90 min, 95 min, 100 min, 105 min, 110 min, 115 min or 120 min.

[0062] In the present invention, the roasting process includes: heating to the roasting temperature at a certain heating rate, and then keeping the roasting temperature for a roasting time. Specifically, the heating rate can be 5 to 15°C / min, preferably 8 to 10°C / min, such as 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min or 10°C / min.

[0063] In a preferred embodiment, step (2) comprises: mixing the glass slag and heavy alcohol incineration ash and grinding them, and then calcining and cooling the obtained glass composite ash to obtain microcrystalline glass.

[0064] In the present invention, the grinding can be performed using conventional equipment in the art; specifically, the grinding is performed in a planetary ball mill.

[0065] In a specific embodiment, the particle size of the glass composite ash obtained by grinding may be 25 to 106 μm, preferably 45 to 75 μm.

[0066] The second aspect of the present invention provides a glass-ceramic prepared by the method described in the second aspect.

[0067] In a preferred embodiment, the density of the microcrystalline glass is 2.08-2.43 g / cm 3 , Vickers hardness is 4.01~4.43GPa, and compressive strength is 223~261Mpa.

[0068] The third aspect of the present invention provides a use of the microcrystalline glass described in the second aspect as a building decoration material.

[0069] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0070] In the following examples, unless otherwise specified, the reagents are all commercially available. The waste glass contains 72.23 wt% SiO2, 13.94 wt% CaO, 8.20 wt% Na2O, 2.92 wt% MgO and 1.07 wt% Al2O3.

[0071] Example 1

[0072] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0073] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0074] The preparation method of glass-ceramics includes:

[0075] (1) 30 g of heavy alcohol incineration ash, 25 g of waste glass, 30 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0076] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0077] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0078] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0079] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0080] Example 2

[0081] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0082] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0083] The preparation method of glass-ceramics includes:

[0084] (1) 35 g of heavy alcohol incineration ash, 25 g of waste glass, 25 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0085] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0086] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0087] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0088] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0089] Example 3

[0090] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0091] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0092] The preparation method of glass-ceramics includes:

[0093] (1) 30 g of heavy alcohol incineration ash, 25 g of waste glass, 25 g of gasification slag, 10 g of B2O3 and 10 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0094] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0095] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0096] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0097] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0098] Example 4

[0099] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0100] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0101] The preparation method of glass-ceramics includes:

[0102] (1) 30 g of heavy alcohol incineration ash, 25 g of waste glass, 30 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0103] (2) heating the raw material powder to 1400° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass to obtain molten glass slag;

[0104] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0105] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0106] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0107] Example 5

[0108] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0109] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0110] The preparation method of glass-ceramics includes:

[0111] (1) 30 g of heavy alcohol incineration ash, 25 g of waste glass, 30 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0112] (2) heating the raw material powder to 1100° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass to obtain molten glass slag;

[0113] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0114] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0115] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0116] Example 6

[0117] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0118] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0119] The preparation method of glass-ceramics includes:

[0120] (1) 30 g of heavy alcohol incineration ash, 30 g of waste glass, 30 g of gasification slag, 5 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0121] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0122] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0123] (4) 90 g of glass slag and 10 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0124] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0125] Example 7

[0126] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0127] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0128] The preparation method of glass-ceramics includes:

[0129] (1) 30 g of heavy alcohol incineration ash, 30 g of waste glass, 30 g of gasification slag, 5 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0130] (2) heating the raw material powder to 1400° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass to obtain molten glass slag;

[0131] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0132] (4) 70 g of glass slag and 30 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0133] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0134] Example 8

[0135] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0136] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0137] The preparation method of glass-ceramics includes:

[0138] (1) 30 g of heavy alcohol incineration ash, 30 g of waste glass, 30 g of gasification slag, 5 g of CaO and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0139] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0140] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0141] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0142] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0143] Example 9

[0144] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0145] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0146] The preparation method of glass-ceramics includes:

[0147] (1) 30 g of heavy alcohol incineration ash, 30 g of waste glass, 30 g of gasification slag, 5 g of B2O3 and 5 g of ZrO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0148] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0149] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0150] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0151] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0152] Example 10

[0153] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0154] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0155] The preparation method of glass-ceramics includes:

[0156] (1) 30 g of heavy alcohol incineration ash, 30 g of waste glass, 30 g of gasification slag, 5 g of CaO and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0157] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 120 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0158] (3) drying the glass slag in a 110° C. forced air drying oven to a constant weight;

[0159] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0160] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 5° C. / min, keeping the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0161] Embodiment 11

[0162] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0163] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0164] The preparation method of glass-ceramics includes:

[0165] (1) 30 g of heavy alcohol incineration ash, 30 g of waste glass, 30 g of gasification slag, 5 g of CaO and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0166] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 120 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0167] (3) drying the glass slag in a 110° C. forced air drying oven to a constant weight;

[0168] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0169] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0170] Example 12

[0171] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0172] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0173] The preparation method of glass-ceramics includes:

[0174] (1) 30 g of heavy alcohol incineration ash, 30 g of waste glass, 30 g of gasification slag, 5 g of CaO and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0175] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 120 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0176] (3) drying the glass slag in a 110° C. forced air drying oven to a constant weight;

[0177] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0178] (5) placing the clinker powder in a corundum crucible and heating the temperature to 800° C. at a heating rate of 8° C. / min, maintaining the temperature for 120 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0179] Comparative Example 1

[0180] The method of Example 1 is followed, except that the heavy alcohol incineration ash in step (1) and step (4) is replaced by pure Na2CO3.

[0181] In this comparative example, the gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0182] The preparation method of glass-ceramics includes:

[0183] (1) 30 g of sodium carbonate, 25 g of waste glass, 30 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0184] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0185] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0186] (4) 80 g of glass slag and 20 g of sodium carbonate were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0187] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0188] Comparative Example 2

[0189] The method of Example 1 is followed, except that only the heavy alcohol incineration ash in step (1) is replaced by pure Na2CO3.

[0190] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0191] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0192] The preparation method of glass-ceramics includes:

[0193] (1) 30 g of sodium carbonate, 25 g of waste glass, 30 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0194] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0195] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0196] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0197] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0198] Comparative Example 3

[0199] The method of Example 1 is followed, except that only the heavy alcohol incineration ash in step (4) is replaced by pure Na2CO3.

[0200] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0201] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0202] The preparation method of glass-ceramics includes:

[0203] (1) 30 g of heavy alcohol incineration ash, 25 g of waste glass, 30 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0204] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0205] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0206] (4) 80 g of glass slag and 20 g of sodium carbonate were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0207] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0208] Comparative Example 4

[0209] The method of Example 1 is followed, except that no alcohol incineration ash is added in step (4).

[0210] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0211] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0212] The preparation method of glass-ceramics includes:

[0213] (1) 30 g of heavy alcohol incineration ash, 25 g of waste glass, 30 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0214] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0215] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0216] (4) grinding 80 g of glass slag on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0217] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0218] Comparative Example 5

[0219] The method of Example 1 is followed, except that no alcohol incineration ash is added in step (1).

[0220] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0221] The gasification slag contains 41 wt % of SiO 2 , 15 wt % of CaO, 15 wt % of Al 2 O 3 , 15 wt % of Fe 2 O 3 and 3 wt % of residual carbon.

[0222] The preparation method of glass-ceramics includes:

[0223] (1) 25 g of waste glass, 30 g of gasification slag, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0224] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0225] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0226] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0227] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0228] Comparative Example 6

[0229] The method of Example 1 is followed, except that no gasified slag is added in step (1).

[0230] In this embodiment, the heavy alcohol incineration ash contains 75 weight % of Na2CO3, 15 weight % of SiO2, 5 weight % of NaCl and 3 weight % of Fe2O3.

[0231] The preparation method of glass-ceramics includes:

[0232] (1) 30 g of heavy alcohol incineration ash, 25 g of waste glass, 10 g of B2O3 and 5 g of TiO2 were mixed and ground into a particle size of 45 to 58 μm using a planetary ball mill to obtain a raw powder;

[0233] (2) heating the raw material powder to 1300° C. at a heating rate of 10° C. / min, keeping the temperature for 90 min, and then quenching the obtained molten glass with water to obtain molten glass slag;

[0234] (3) drying the glass slag in a 105° C. forced air drying oven to a constant weight;

[0235] (4) 80 g of glass slag and 20 g of heavy alcohol incineration ash were mixed and ground on a planetary ball mill to a particle size of 45 to 58 μm to obtain clinker powder;

[0236] (5) placing the clinker powder in a corundum crucible and heating the temperature to 900° C. at a heating rate of 8° C. / min, maintaining the temperature for 90 min, and then cooling the temperature naturally to obtain microcrystalline glass.

[0237] Test Example 1

[0238] The density, hardness and compressive strength of the glass-ceramics prepared in Examples 1-12 and Comparative Examples 1-6 were tested, and the results are shown in Table 1.

[0239] The density test method is: the density of the microcrystalline glass sample is measured by the pycnometer method. Test process: weigh the sample mass m 物 , the mass of the pycnometer filled with water is m 水 , put the sample in the specific gravity bottle and fill it with water 总 , press to calculate the sample density:

[0240]

[0241] The hardness test method is: use Vickers hardness tester to measure the hardness of the sample. Sample preparation: mount, grind and polish the sample. Test conditions: load 200g, load time 10s, measure 5 times and take the average value.

[0242] The compressive strength test method is: using a universal testing machine to measure the compressive strength of the sample.

[0243] Table 1

[0244]

[0245]

[0246] It can be seen from Table 1 that the density, hardness and strength of the microcrystalline glass prepared according to the method of the present invention are better than those of the comparative example.

[0247] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing glass-ceramics, characterized in that: The method comprises the following steps: (1) mixing, melting and cooling heavy alcohol incineration ash, waste glass, gasification furnace slag, flux and crystal nucleating agent to obtain glass molten slag, wherein the melting temperature is 1100-1400° C.; (2) mixing the glass slag and heavy alcohol incineration ash, roasting and cooling to obtain glass-ceramics, wherein the roasting temperature is 800 to 1000° C.; Wherein, the heavy alcohol incineration ash contains 50-85 weight % of Na2CO3 and 5-20 weight % of SiO2; The gasification slag contains 20 to 45 wt % of SiO2, 10 to 25 wt % of CaO and 8 to 15 wt % of Al2O3.

2. The method according to claim 1, characterized in that The heavy alcohol incineration ash contains 50-85 weight % of Na2CO3, 5-20 weight % of SiO2, 5-10 weight % of NaCl and 2-10 weight % of Fe2O3.

3. The method according to claim 1 or 2, characterized in that: The gasification slag contains 20 to 45 weight % of SiO2, 10 to 25 weight % of CaO, 8 to 15 weight % of Al2O3, 5 to 15 weight % of Fe2O3 and 3 to 37 weight % of residual carbon.

4. The method according to any one of claims 1 to 3, characterized in that: In step (1), based on the total weight of heavy alcohol incineration ash, waste glass, gasification slag, flux and crystal nucleating agent, the content of the heavy alcohol incineration ash is 20-40% by weight, the content of the waste glass is 25-30% by weight, the content of the gasification slag is 25-30% by weight, the content of the flux is 5-10% by weight, and the content of the crystal nucleating agent is 5-10% by weight.

5. The method according to any one of claims 1 to 4, characterized in that: In step (1), the flux is selected from one or more of B2O3, Na2O, K2O, CaO and BaO.

6. The method according to any one of claims 1 to 5, characterized in that: In step (1), the nucleating agent is selected from one or more of Fe2O3, ZrO2, NaF, Cr2O3 and TiO2.

7. The method according to any one of claims 1 to 6, characterized in that: In step (1), the melting conditions include: melting temperature of 1200-1300° C.; melting time of 30-150 min, preferably 60-120 min; heating rate of 5-20° C. / min, preferably 10-15° C. / min.

8. The method according to any one of claims 1 to 7, characterized in that: Step (1) comprises: mixing heavy alcohol incineration ash, waste glass, gasification furnace slag, flux and crystal nucleating agent and grinding them, and then melting, cooling and drying the obtained raw powder to obtain glass slag.

9. The method according to claim 8, characterized in that The particle size of the raw powder obtained by grinding is 25 to 106 μm, preferably 45 to 75 μm.

10. The method according to claim 8 or 9, characterized in that: The cooling method is water quenching or natural cooling; Preferably, the drying temperature is 90-120°C.

11. The method according to any one of claims 1 to 10, characterized in that: In step (2), based on the total weight of the glass slag and the heavy alcohol incineration ash, the content of the glass slag is 65-95% by weight, and the content of the heavy alcohol incineration ash is 5-35% by weight.

12. The method according to any one of claims 1 to 11, characterized in that: The calcination conditions include: a calcination temperature of 850-950° C.; a calcination time of 60-150 min, preferably 90-120 min; and a heating rate of 5-15° C. / min, preferably 8-10° C. / min.

13. The method according to any one of claims 1 to 12, characterized in that: Step (2) comprises: mixing the glass slag and heavy alcohol incineration ash and grinding them, and then roasting and cooling the obtained glass composite ash to obtain microcrystalline glass.

14. The method according to claim 13, characterized in that The particle size of the ground glass composite ash is 25 to 106 μm, preferably 45 to 75 μm.

15. Glass-ceramics prepared by the method described in any one of claims 1 to 14.

16. The glass-ceramic according to claim 15, characterized in that: The density of the microcrystalline glass is 1.87-2.43 g / cm 3 , Vickers hardness is 3.49~4.43GPa, and compressive strength is 197~261Mpa.

17. Use of the microcrystalline glass according to claim 15 or 16 as a building decoration material.

Citation Information

Patent Citations

  • Method for producing foam microcrystal glass by utilizing composite industrial residue and product

    CN102838283A

  • Cordierite-based nanometer glass-ceramic and preparation method thereof

    CN104496186A

  • Method for preparing glass ceramics by utilizing waste rare-earth polishing powder

    CN107555799A

  • Green glass ceramic and preparation method thereof

    CN107879633A

  • Vitreous body preparation method, harmless treatment method for hazardous waste incineration slag and waste incineration fly ash

    CN112661407A